Blood-Based MicroRNAs in Psychotic Disorders—A Systematic Review - Ștefania-Alexandra Grosu; Maria Dobre; Elena Milanesi; Mihail Eugen Hinescu (Biomedicines, 2023)
Psychotic disorders are a heterogenous class of mental illness, with an intricate pathophysiology, involving genetics and environmental factors, and their interaction. The identification of accessible biomarkers in bodily systems such as blood may lead to more accurate diagnosis, and more effective treatments targeting dysfunctional pathways, and could assist in monitoring the disease evolution. This systematic review aims to highlight the dysregulated microRNAs (miRNAs) in the peripheral blood of patients with psychotic disorders. Using the PRISMA protocol, PubMed and Science Direct databases were investigated and 22 articles were included. Fifty-five different miRNAs were found differentially expressed in the blood of psychotic patients compared to controls. Seventeen miRNAs (miR-34a, miR-181b, miR-432, miR-30e, miR-21, miR-137, miR-134, miR-7, miR-92a, miR-1273d, miR-1303, miR-3064-5p, miR-3131, miR-3687, miR-4428, miR-4725-3p, and miR-5096) were dysregulated with the same trend (up- or down-regulation) in at least two studies. Of note, miR-34a and miR-181b were up-regulated in the blood of psychotic patients in seven and six studies, respectively. Moreover, the level of miR-181b in plasma was found to be positively correlated with the amelioration of negative symptoms. The panel of miRNAs identified in this review could be validated in future studies in large and well-characterized cohorts of psychotic patients.